2019
DOI: 10.1016/j.phymed.2018.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Ailanthone inhibits cell growth and migration of cisplatin resistant bladder cancer cells through down-regulation of Nrf2, YAP, and c-Myc expression.

Abstract: Background: Ailanthone (Aila) is a natural active compound isolated from the Ailanthus altissima,-inhibitory effect against several cancer cell lines. Advanced bladder cancer is a common disease characterized by a frequent onset of resistance to cisplatin-based therapy. The cisplatin (CDDP) resistance is accompanied by an increase in Nrf2 protein expression which contributes to conferring resistance. Recently, we demonstrated a crosstalk between Nrf2 and YAP. YAP has also been demonstrated to play an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 33 publications
2
47
0
Order By: Relevance
“…In various types of cancers, it has been shown that the adaptive response mediated by Nrf2 contributes to the resistance towards chemotherapeutic pro-oxidant drugs, such as cisplatin (CDDP). Recently, we provided evidence on its key role in sustaining CDDP resistance in bladder cancer [ 4 , 5 , 6 ], in agreement with other reports [ 7 ]. For these reasons, Nrf2 can be a promising target to overcome chemoresistance.…”
Section: Introductionsupporting
confidence: 90%
“…In various types of cancers, it has been shown that the adaptive response mediated by Nrf2 contributes to the resistance towards chemotherapeutic pro-oxidant drugs, such as cisplatin (CDDP). Recently, we provided evidence on its key role in sustaining CDDP resistance in bladder cancer [ 4 , 5 , 6 ], in agreement with other reports [ 7 ]. For these reasons, Nrf2 can be a promising target to overcome chemoresistance.…”
Section: Introductionsupporting
confidence: 90%
“…The combination of anti-tumor agents should be able to produce synergistic or additive therapeutic e cacies, reduced side effects and minimal drug resistance. Experimental strategies that investigate combinational therapy of CDDP with natural plant extracts/plant-derived agents to maintain the desired antitumor e cacy have been reported [9,36,37]. In this study, HWG in combined with CDDP inhibits the invasion of these RCC cells, especially at a concentration of more than 100 mg/mL and inhibited the wound-healing migration of these RCC cells, especially at a concentration of more than 200 mg/mL.…”
Section: Discussionmentioning
confidence: 74%
“…The combination of anti-tumor agents should be able to produce synergistic or additive therapeutic efficacies, reduced side effects and minimal drug resistance. Experimental strategies that investigate combinational therapy of CDDP with natural plant extracts/plant-derived agents to maintain the desired antitumor efficacy have been reported [9,36,37]. In this study, HWG in combination with CDDP inhibits the invasion of these RCC cells, especially at a concentration of more than 100 µg/mL and inhibited the wound-healing migration of these RCC cells, especially at a concentration of more than 200 µg/mL.…”
Section: Discussionmentioning
confidence: 78%